Annotations: walking, ocean acidification. - Galvez, Pia (Zenodo, 2024)
Annotations is an ongoing artwork in progress. research-creation hydrological hazards and ocean acidification Figure 1. Ideogram, manipulated digital image. Superposition of Panchromatic image from the IRS-P5 Cartosat-1 dataset and SPM.5 figure from the Summary for Policymakers, Synthesis Report (SYR), IPCC Sixth Assessment Report (AR6). Figure 2. Screenshot. Miniatures of non-manipulated digital images (.raw) from a coastal walk. North Atlantic region, coinciding with the IRS-P5 Cartosat-1 dataset from Figure 1.